A New Technique to Identify the Location of the Mucogingival Junction on Computer Tomographic Scans Before Implant Placement. Issue 3 (June 2015) - Tarnow, Dennis P.; Pérez, José M.; Ghamid, Salah S.; Manasse, Maryse; Froum, Stuart J.; Shabeesh, Maree; Cho, Sang-Choon
Abstract : A new technique is presented to identify the location of mucogingival junction (MGJ) on CT scans before implant placement. This case report describes the step-by-step fabrication of a radiographic template, which when used in conjunction with CT scans enables the clinician to locate the position of MGJ before implant placement and predict the amount of keratinized tissue (KT) that will be present around an implant. Using this technique, the operator can determine whether or not flapless implant surgery may be a treatment option and whether simultaneous soft tissue augmentation will be necessary at the time of implant placement to establish an adequate band of KT.